Innate Anti-microbial and Anti-chemotaxis Properties of Progranulin in an Acute Otitis Media Mouse Model - Wang, Zimeng; He, Qian; Zhang, Xinxin; Ma, Yurong; Fan, Fangmei; Dong, Yilin; Xu, Wenchun; Yin, Yibing; He, Yujuan (Frontiers in Immunology, 2018)
Acute otitis media (AOM) is one of the most common infectious diseases primarily caused by Streptococcus pneumoniae (S.pn) among children. Progranulin (PGRN) is a multifunctional growth factor widely expressed in various tissues and cells. Studies have confirmed that PGRN is involved in the development of a variety of inflammatory diseases. We found that the expression of PGRN increased significantly in the middle ear of wild mice with AOM. However, its physiological functions in AOM still remain unknown. To examine the role of PGRN during AOM, we established an acute otitis media model in both C57BL/6 wild mice and PGRN-deficient (PGRN-/-) mice via transbullar injection with S.pn clinical strain serotype 19F. Interestingly, we observed dual results: on one hand, macrophage recruitment notably increased in PGRN-/- mice compared with WT mice; on the other hand, the overall bacterial clearance was surprisingly dampened in PGRN-/- mice. The enhanced recruitment of macrophages was associated with increased production of chemokine (C-C motif) ligand 2 (CCL2), while the decreased bacterial clearance was associated with impaired endocytosis capacity of macrophages. The scavenging ability of bacteria in PGRN-/- mice was recovered with administration of recombinant PGRN. These results suggested a novel dual role of PGRN in affecting the activities of macrophages.